American Russian relations and their impact on the Regional Stability in the Middle East (2011-2018)) Case Study Syria ( - AlZabin, Areej (Dirasat: Human and Social Sciences, 2021)
In light of the Arab Revolutions and the subsequent crises, an evident fierce competition dominated the Middle East. It became televised and made the headlines in main newspapers. Websites raced to transfer the latest of such conflict once it took place, and every moment after the Iranian Saudi Competition, which dominated the regional arena since the Arab Spring in 2011. However, in the past few years, namely since 2013, the US Russian rivalry to dominate the Middle East surfaced. Apparently, this competition never took the form of a conflict yet was manifested in a sort of regional understanding, which is reflected in defining areas of influence, and allowing the other party in addition to facilitating his task of controlling other areas of influence. The researcher chose Syria as a study case. Among the most important findings of the researcher is that: The Middle East represents a region of vital interests for the United States of America, on top of which is access to oil and ensuring Israel's security. This corresponds to the interest of Russia, which has intervened in Syria by providing support to the Syrian state. This has also strengthened Russia’s influence in Syria in particular, as a prelude to extending its influence to other countries, which was positively reflected in the interest of Russia’s international standing. Among the most important recommendations made by the researcher. The countries of the Middle East region are considered to have a deep civilization steeped in history and provided humanity with the foundations of modern science and technological civilization in which we live today. Therefore, these countries should return to this influential and effective historical role in the international community.